Philosophy : A Short, Visual Introduction - Paeth, Scott (Christianity and the liberal arts., 2015)
Philosophy: A Short, Visual Introduction is the ideal path to understanding the philosophical ideas that influence Christian theology. Scott Paeth's fast-paced introduction covers the most important movements and thinkers with precision and clarity. The major ideas are creatively illustrated by artist Joseph Novak, whose crisp, modern style brings big concepts to life for readers. The result is an articulate, no-nonsense approach that guides readers from the ideas of ancient philosophers to contemporary thinkers and movements that impact Christians today. Philosophy is part of the Christianity and the Liberal Arts series, which recognizes that many Christians are eager to deepen their understanding of the liberal arts, yet have limited time to do so. By reviewing key fields--philosophy, history, literature, world religions, and the arts--in a concise, creative way, books in the Christianity and the Liberal Arts series will inspire new insights for a new generation of Christian life and ministry.